Patient trust in the health system, Internet information searching and the patient-provider relationship - Mainous, Arch G.; Liu-Galvin, Rachel; Durden, Barbara; Yin, Lu; Saguil, Aaron A. (Frontiers in Medicine, 2025)
ImportanceA positive patient-provider relationship is critical to the delivery of quality healthcare.ObjectivesTo examine the association between patients’ level of trust in the healthcare system, Internet information searching and the patient-provider relationship.MethodsAnalysis of adult patients aged ≥ 18 in the US nationally representative Health Information National Trends Survey (HINTS 7-2024) (unweighted n = 2,510; weighted n is > 87 million). The patient-provider relationship was assessed focusing on discussing health information found on the Internet with their provider: (1) whether the provider was open to the discussion, (2) whether the provider was respectful, and (3) whether the interaction worsened. Respondents were asked how much they trust the healthcare system.ResultsThe proportion of patients with high trust in the healthcare system was 31%. Patients with low trust (17%) were more likely than those with high trust (3%) to perceive that in visits with their healthcare provider, talking about information found on the Internet, the patient-provider interaction became worse (p < 0.01). In logistic regressions controlling for multiple covariates, low trust in the healthcare system was associated with an increased likelihood that in visits with their healthcare provider, talking about information found on the Internet, the patient-provider interaction became worse (OR 6.76; 95% CI 2.35, 19.44).ConclusionPatients with low trust in the healthcare system are at greater risk of having less than optimal relationships with their healthcare provider due to discussions over health information found on the Internet.